Polysulfide Synthesis Using Waste Cooking Palm Oil via Inverse Vulcanization - Nayeem, Abdullah; Mohd Faizal, Ali; Jun Haslinda, Shariffuddin (Wiley, 2022)
Elemental sulfur and waste cooking palm oil (WCO) are abundant industrial by-products from petrochemical and food processing industries, respectively. WCO was used as a crosslinker to prepare a high-sulfur-content polymer through inverse vulcanization. Polysulfides were generated under vigorous stirring of WCO with elemental sulfur at different temperatures, crosslinking ratios, and reaction times. The physicochemical properties of the produced polysulfides were determined and the thermal stability was analyzed. The FTIR spectra including the breakdown of C=C and formation of C–S bond confirmed the change of functional groups between WCO and produced polymer. The effect of saturated and unsaturated triglycerides of WCO is clearly visible in SEM micrographs. The polysulfide with a 70 wt % sulfur feed ratio showed excellent morphological and thermal properties.